Mitoprotection preserves the renal vasculature in porcine metabolic syndrome. Issue 7 (27th May 2018) - Eirin, Alfonso; Hedayat, Ahmad F.; Ferguson, Christopher M.; Textor, Stephen C.; Lerman, Amir; Lerman, Lilach O.
Abstract : New Findings: What is the central question of this study ? We hypothesized that chronic mitoprotection would decrease renal vascular remodelling and dysfunction in swine metabolic syndrome. What is the main finding and its importance ? This study shows that experimental metabolic syndrome exerts renal microvascular and endothelial cell mitochondrial injury, which were attenuated by mitoprotection, underscoring the contribution of mitochondrial injury to the pathogenesis of metabolic syndrome‐induced vascular damage. Abstract: The metabolic syndrome (MetS) induces intrarenal microvascular disease, which may involve mitochondrial injury. The mitochondrial cardiolipin‐targeting peptide elamipretide (ELAM) improves the microcirculation in post‐stenotic kidneys, but its ability to attenuate MetS‐induced renal vascular damage is unknown. We hypothesized that chronic treatment with ELAM would decrease renal vascular remodelling and function in swine MetS. Pigs were studied after 16 weeks of diet‐induced MetS, MetS treated for the last 4 weeks with daily injections of ELAM (0.1 mg kg −1 ), and lean control (Lean) animals ( n = 6 each). Single‐kidney regional perfusion, blood flow and glomerular filtration rate were measured with multi‐detector computed tomography (CT). Peritubular capillary (PTC) endothelial cell (EC) mitochondrial density and cardiolipin content were assessed in situ, as were PTC‐EC apoptosis and oxidative stress. The spatial density of PTCs (Haematoxylin and Eosin staining) and renal microvessels (micro‐CT), and renal artery endothelial function (organ bath) were characterized. Regional perfusion and serum creatinine were preserved in MetS pigs, but renal blood flow and glomerular filtration rate were higher compared with Lean. Mitochondrial density and cardiolipin content were diminished in MetS PTC‐ECs, but improved in ELAM‐treated pigs, as did PTC density. Elamipretide also attenuated PTC‐EC oxidative stress and apoptosis. Furthermore, ELAM improved renal microvascular density, decreased microvascular remodelling and restored endothelial nitric oxide expression and endothelium‐dependent relaxation of renal artery segments. In conclusion, MetS‐induced mitochondrial alterations might contribute to renal PTC and microvascular loss and might impair renal artery endothelial function in pigs. Mitoprotection with ELAM preserved a hierarchy of renal vessels, underscoring its potential to ameliorate renal vascular injury in MetS. Abstract :